Basic sonographic examination of the fetal brain at 11–13 weeks' gestation: Rationale for a simple and reliable four‐step technique. Issue 2 (13th February 2023) - Sepulveda, Waldo; Garcia‐Rodriguez, Raquel; Martinez‐Ten, Pilar; Tonni, Gabriele; Grisolia, Gianpaolo; Meagher, Simon
Abstract: The widespread incorporation of first‐trimester scanning between 11 and 13 weeks' gestation has shifted from the screening of chromosomal abnormalities, mainly by measuring nuchal translucency thickness and visualization of the nasal bone, to a more detailed study of the fetal anatomy leading to early detection of several structural congenital anomalies. This goal can be improved by the routine and focused sonographic assessment of specific anatomic planes and the identification of distinctive landmarks that can help disclosing a particular, non‐evident condition. In this article we present the basis for a basic, early examination of the fetal brain during screening using a four‐step technique, which can be readily incorporated during the first‐trimester scan. The technique includes the focused visualization of the cranial contour, choroid plexuses of the lateral ventricles and midline, aqueduct of Sylvius, brainstem, fourth ventricle, and the choroid plexus of the fourth ventricle. The rationale for this approach is presented and discussed. Abstract : We discuss the basis for a basic, early examination of fetal brain during the first‐trimester scan using a four‐step technique. This includes the focused visualization of the cranial contour, choroid plexuses of the lateral ventricles, midline, aqueduct of Sylvius, brainstem, fourth ventricle, and the choroid plexus of the fourth ventricle.